ETIOLOGY AND TREATMENT TACTICS OF MASTITIS, A COMMON DISEASE IN WOMEN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article describes the methods of early detection of mastitis, a common disease of the mammary gland in women. The significance of the currently conducted examinations is revealed. The methods of self-examination of women in everyday life are discussed.